Dapsone Hypersensitivity Syndrome is a Rare Cause of Non-leprosy Induced Pyrexia of Unknown Origin - Keyal, Niraj Kumar; Jha, Sudhakar; Saurabh, Shishir; Kafle Chaulagain, Meena (Med Phoenix, 2025)
Introduction: Pyrexia of unknown origin is a common cause of fever that requires admission and extensive workup for diagnosis and management in both the intensive care unit and the general ward. We present a case of a 35-year-old male with a past history of Lichen Planus under Dapsone therapy who presented with fever associated with chills and rigor, headache, skin rash, multiple swellings all over the body, shortness of breath, and hypotension. The patient was started on fluids and broad-spectrum antibiotics. Laboratory investigations, radiological investigation were done, and diagnosed as Dapsone hypersensitivity syndrome. The patient was treated with prednisone and antibiotics. He was discharged after 10 days of hospital admission. The patient was advised to follow up at 2 weeks, and prednisone was gradually tapered off during the visit. Drug history should be part of the history that helps in treating patients presenting with pyrexia of unknown origin.